Responsabilidade social na construção civil - César, Vivian Aparecida Blaso Souza Soares (2011)
In the decade of 90 to the marginal of River Pinheiros was born a new city, taken root of technological high commercial buildings in the region of the Av. Engenheiro Luiz Carlos Berini and Av. Faria Lima the icone a ready city globalized for attend to that new world economic order. In this context, that dissertation has for objectives: put into context the incorporation of the notions of social responsibility of the companies; verify as the social responsibility is practiced in the sector of the civil construction in São Paulo and evaluate the rank of practical compromise of the sector with the subject of the sustainability that today present is done in the talk of the companies and in the media with his public